Analisis Kualitas Air Laut Sebagai Bahan Baku Garam di Provinsi Aceh - Bahagia Bahagia; Afrizal Afrizal (Fakultas Teknik, 2019)
Currently barriers are still faced by salt farmers because they still use traditional technology in salt production so traditional farmers are less competitive than other modern salt products. The method of data collection was carried out by analyzing sea water quality survey and test at the Research and Development Agency of the Industrial Research and Standardization Center of Industrial in Banda Aceh. This study aims to obtain the results of measuring the quality of sea water that will be used as old water as raw material for salt. The results showed that the highest degree of Bauma came from the sample of Alue Rambut Lembah Sabil and Sejahtera Manggeng in the amount of 4 Be. Furthermore, the highest NaCl level originated in the Sejahtera Mangeng sample by 3%, the highest iodine (KiO3) from the Sejahtera Manggeng sample of 0.421 mg / kg. The biggest lead (Pb) test results came from the Sejahtera Mangeng sample of 0.2224 mg / L. Furthermore, the test results of Cadmium (Cd), Water Mercury (Hg) and Arsenic (As) with the AAS method are at the detection limit of the test equipment at 0,0004 mg / L, 0,0005 mg / L and 0 0002 mg / L